Implementasi Media Pembelajaran Animasi Zep Quiz Dalam Mata Pelajaran Pendidikan Agama Hindu Dan Budi Pekerti Pada Minat Belajar Siswa Kelas VII F di SMP Negeri 1 Denpasar - Putu Eka Putri Jayanti; Heny Perbowosari; Putu Ayu Septiari Dewi (Ameena Journal, 2026)
The development of digital technology has encouraged teachers to utilize interactive learning media in the classroom. One of the learning media that can be used is Zep Quiz, an animated and game-based learning platform capable of creating a more engaging learning atmosphere. This study aims to determine the implementation of animated learning media Zep Quiz, the obstacles and efforts in its implementation, and its implications for students’ learning interest in Hindu Religious Education and Character subjects in class VII F of SMP Negeri 1 Denpasar. This study used a qualitative approach with purposive sampling technique. Data collection techniques were carried out through interviews, observations, documentation, and literature studies. The results showed that the implementation of Zep Quiz was carried out through planning, implementation, and evaluation stages integrated into the Teaching Module. The use of Zep Quiz was able to create interactive learning, increase student participation, and foster students’ learning interest. Obstacles encountered included unstable internet networks, limited time in preparing media, and students being distracted by game elements. The efforts made by teachers included coordinating with the school IT team, preparing quiz templates, and providing learning guidance during activities. The use of Zep Quiz also had implications for the development of teacher creativity, more structured learning, and easier evaluation of student learning outcomes.